Cattle owners' perceptions of African bovine trypanosomiasis and its control in Busia and Kwale districts of Kenya - Machila, N.; Eisler, M.C.; Wanyangu, S.W.; McDermott, John J.; Welburn, S.C.; Maudlin, I. (International Society for Veterinary Epidemiology and Economics, 2000)
Bovine trypanosomiasis caused by pathogenic trypanosomes, and cyclically transmitted by tsetse flies, is considered to be a major disease constraint to livestock production in sub-Saharan Africa, preventing full use of the land to feed the rapidly increasing human population. Privatisation of veterinary services in Africa has led to a situation where drug administration is in the hands of farmers or extension workers, who are unskilled in differential diagnosis and lack knowledge on appropriate drug user. This indiscriminate use of trypanocides is undesirable because it is uneconomical to treat uninfected animals, and misuse and overuse of trypanocides may be associated with the Development of drug resistance*' and occasionally with toxicity5. The objective of this study was to obtain data from cattle owners on their current knowledge, attitude and practices concerning on-farm disease diagnosis and treatment, and their perceptions of the importance and control of trypanosomiasis and other endemic diseases in Busia and Kwale Districts of Kenya.